Differences in Gut Microbiome in Hospitalized Immunocompetent vs. Immunocompromised Children, Including Those With Sickle Cell Disease - Mohandas, Sindhu; Soma, Vijaya L.; Tran, Thi Dong Binh; Sodergren, Erica; Ambooken, Tresa; Goldman, David L.; Weinstock, George; Herold, Betsy C. (Frontiers in Pediatrics, 2020)
Abstract Background: Gut microbial diversity and composition play important roles in health. This cross-sectional study was designed to test the hypothesis that hospitalized children who may be relatively immunocompromised (IC), defined as those with cancer, sickle cell disease (SCD), transplantation, or receiving immunosuppressive therapy) would have decreased microbial diversity, increased Clostridioides difficile colonization and different species composition compared to non-immunocompromised (Non-IC) children admitted to the same pediatric unit. Methods: A stool sample was obtained within 72 hours of admission to a single unit at The Children’s Hospital at Montefiore, Bronx, NY from March 2016 to February 2017 and the microbiome assessed by 16S rRNA sequencing. C. difficile colonization was assessed by glutamate dehydrogenase antigen and toxin polymerase chain reaction assays. Results: Stool samples were obtained from 69 IC (32 SCD, 19 cancer, 9 transplantation and 9 other) and 37 Non-IC patients. There were no significant differences in microbial alpha diversity and C. difficile colonization comparing IC versus non-IC patients. Lower alpha diversity, however, was independently associated with the use of proton pump inhibitors or antibiotics, including prophylactic penicillin in patients with SCD. Differences in specific species abundances were observed when comparing IC versus non-IC patients, particularly children with SCD. Non-IC patients had increased abundance of commensals associated with health including Alistipes putredinis, Alistipes ihumii, Roseburia inulinivorans, Roseburia intestinalis and Ruminococcus albus (p < 0.005). Conclusions: Antibiotics and proton pump inhibitors, which were more commonly used in IC children, were identified as risk factors for lower microbial diversity. Non-IC patients had higher abundance of several bacterial species associated with health. Longitudinal studies are needed to determine the clinical significance of these differences in gut microbiome.